Analisis Kualitas Pelayanan Antar Jemput Produk Tabungan Terhadap Tingkat Kepuasan Nasabah (Studi Kasus Pada BPRSyari’ah Harta Insan Karimah Cabang Cikarang) - Suchi Wati Dewi; Rafika Rahmawati (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2021)
The development of Islamic banks this time, the quality of service and customer satisfaction isa key factor that will become a competitive advantage of a company. Therefore a company is largelydetermined by the ability of banks to provide the best quality service compared to its competitors.This research is a descriptive qualitative approach. The object of this research is BPRS Harta InsanKarimah Branch Of Cikarang. While the subject is a customer of BPRS Harta Insan Karimah BranchOf Cikarang, amounting to 5 (five) people with 1 (one) the informant of BPRS Harta Insan KarimahBranch Of Cikarang. Methods of data collection by observation, interview and documentation. Forvalidation data using triangulation sources. Data analysis techniques there are three, namely: DataReduction, Presentation Of Data, and nteresting Conclusion and Verification. These results indicatethat (1) the service quality of BPRS Harta Insan Karimah Branch Of Cikarang is quite satisfactory forour customers. However,there are still factors that make customers feel quite satisfied, namely on timeconstraints. (2) There are four factors that determine the quality service pick-up of savings productson customer satisfaction at BPRS Harta Insan Karimah Branch Of Cikarang, namely Responsivness,Reliability, Assurance, and finally Emphaty (Empathy). (3) The quality level of savings product pick-upon customer satisfaction is carried out by BPRS HIK Cikarang Branch, namely by providing the bestquality service and fulfilling customer desires with that customers will be satisfied with the servicesprovided by BPRS HIK Cikarang Officers.